Deconstructing Sins from the Moral Compass of Don Carlos Cobello in F. Sionil Joseâ€™s Sins - Edaniol, Aubrey Anne C.; Medina, Benedict O. (OKARA: Jurnal Bahasa dan Sastra, 2022)
The novel â€œSinsâ€ by F. Sionil Jose depicts the adventurous life of an affluent man whose confessions rationalize the sins he committed as judged only against social standards but ironically narrates the dire consequences as moral concepts. The study aims to deconstruct the prevailing theme of sins as social notions to prove that sins are moral constructs and to teach that morality is an inherent feature of man’s mortality. To establish these contradicting ideologies, the study utilized the deconstruction approach in literary criticism by Jacques Derrida. Deconstructionism exposes embedded ideologies by revealing inconsistencies in the text. Specifically, content analysis was integrated to examine words and phrases in-depth to analyze rooted messages. This paper found out that the novel claims incest, premarital sex, and sexual exploitation as sins established only by society and should be judged by it and not beyond it. However, through investigating its instabilities, it was revealed that the novel actually justifies sins against the character’s morality because of his belief in mortality as the recipient of suffering, forgiveness, retributive punishments, and even conscience. Thus, the novel inculcates that sins are not just mere social concepts, they are the foremost moral constructs.